Canadian Regulatory Perspective on Next Generation Risk Assessments for Pest Control Products and Industrial Chemicals - Bhuller, Yadvinder; Ramsingh, Deborah; Beal, Marc; Kulkarni, Sunil; Gagne, Matthew; Barton-Maclaren, Tara S (Frontiers in Toxicology, 2021)
In 2012, the Council of Canadian Academies published the expert panel on integrated testing of pesticide’s report titled: Integrating emerging technologies into chemical safety assessment. This report was prepared for the Government of Canada in response to a request from the Minister of Health and on behalf of the Pest Management Regulatory Agency. It examined the scientific status of the use of integrated testing strategies for the regulatory health risk assessment of pesticides while noting the data-rich/poor dichotomy that exists when comparing pesticide formulations to most industrial chemicals. It also noted that the adoption of integrated approaches to testing and assessment (IATA) strategies may refine and streamline testing of chemicals, as well as improve results in the future. Moreover, the experts expected to see an increase in the use of integrated testing strategies over the next decade, resulting in improved evidence-based decision-making. Subsequent to this report, there has been great advancements in IATA strategies, which includes the incorporation of adverse outcome pathways (AOPs) and new approach methodologies (NAMs). This perspective provides the first Canadian regulatory update on how Health Canada is also advancing the incorporation of alternative, non-animal strategies, using a weight of evidence approach, for the evaluation of pest control products and industrial chemicals. It will include specific initiatives and describe how this work is leading to the creation of next generation risk assessments. It also reflects Health Canada’s commitment towards implementing the 3Rs of animal testing: reduce, refine and replace the need for animal studies, whenever possible.